Pengembangan Ekonomi Desa Padanaan dengan Wirausaha Keripik Kulit Pisang di Kabupaten Sumedang - Bella Oktavianita; Faizah Izdihar; Neneng Hasanah (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
One form of effort that is possible to be done by housewives without is entrepreneurship in making chips. Chips that are often found among people are banana chips because they have good prospects and are very easy to find, especially in Indonesia. During this time, the community has not utilized the banana plant as a whole and only focused on the fruit. In fact, many are used from banana plants, one of which is banana peel. Banana peels only become organic waste that has a large amount. Through this community service, there will be a direct socialization and demonstration on the use of banana peels as a way of economic development in Padanaan Village, Paseh District, Sumedang Regency. This service in making processed chips from banana peels has a positive impact. In addition to increasing the economic value of banana weevil, it also provides benefits to partners, namely increasing the skills and knowledge of partners related to the production of processed products from banana trees, this activity gained positive enthusiasm in the activity and then made banana peel chips as a business opportunity for Padanaan Village. Keywords: Chips, banana, Padanaan Village